2018
DOI: 10.3390/biom8030051
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactamase Tools for Establishing Cell Internalization and Cytosolic Delivery of Cell Penetrating Peptides

Abstract: The ability of cell penetrating peptides (CPPs) to deliver biologically relevant cargos into cells is becoming more important as targets in the intracellular space continue to be explored. We have developed two assays based on CPP-dependent, intracellular delivery of TEM-1 β-lactamase enzyme, a functional biological molecule comparable in size to many protein therapeutics. The first assay focuses on the delivery of full-length β-lactamase to evaluate the internalization potential of a CPP sequence. The second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Dowdy and co-workers have used this assay to screen a panel of hydrophobic peptides for their capacity to enhance endosomal escape . Stone et al developed a similar complementation assay by using TEM-1 β-lactamase and a FRET-based substrate CCF2-AM . A CPP of interest is fused to the N-terminal fragment of β-lactamase (N-BLA_SpyT) while the C-terminal fragment (SpyC_C-BLA) is expressed inside cells.…”
Section: Methods For Assessing Cell-permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Dowdy and co-workers have used this assay to screen a panel of hydrophobic peptides for their capacity to enhance endosomal escape . Stone et al developed a similar complementation assay by using TEM-1 β-lactamase and a FRET-based substrate CCF2-AM . A CPP of interest is fused to the N-terminal fragment of β-lactamase (N-BLA_SpyT) while the C-terminal fragment (SpyC_C-BLA) is expressed inside cells.…”
Section: Methods For Assessing Cell-permeabilitymentioning
confidence: 99%
“…376 Stone et al developed a similar complementation assay by using TEM-1 β-lactamase and a FRET-based substrate CCF2-AM. 377 A CPP of interest is fused to the N-terminal fragment of β-lactamase (N-BLA_SpyT) while the C-terminal fragment (SpyC_C-BLA) is expressed inside cells. If the CPP successfully delivers the Nterminal fragment into the cytosol, the SpyTag/SpyCatcher pair brings together the two fragments to form a functional βlactamase, which cleaves CCF2-AM and shifts its fluorescence from green to blue.…”
Section: Protein Complementationmentioning
confidence: 99%
“…Birch et al tested seven different fluorophores of various structures with penetratin and were able to draw the following general conclusions: fluorophore-penetratin conjugates exert strong structure-dependent reduction in viability of several mammalian cell types as compared to non-labelled penetratin; effects on membrane integrity, as well as intracellular distribution patterns, differed among the conjugates; neutral hydrophobic fluorophores or negatively charged fluorophores conferred less cytotoxicity as compared to the effect exerted by positively charged, hydrophobic fluorophores. To improve the detection of cell uptake of CPPs in the cytosol, two β-lactamase fluorogenic assays were developed (Ston et al, 2018). In one assay, a complete functional enzyme β-lactamase is delivered into cells by CPP.…”
Section: Fluorescencementioning
confidence: 99%
“…201,202,204 A similar system was reported that uses an acetoxymethyl ester of coumarin-cephalosporin-fluorescein (CCF2-AM), which is a FRET-based substrate probe developed specifically for Escherichia coli TEM-β-lactamase. 203,[205][206][207] CCF2-AM exhibits green fluorescence, but its emission wavelength switches to blue upon cleavage by cytosolic β-lactamase, 208 which was monitored by fluorescence microscopy and flow cytometry. 209'210 The cytosolic calcein release assay' originally developed to measure cell viability' involves either covalently labeling the cargo with calcein-AM, or coencapsulating the cargo with an acetoxymethyl ester version of calcein (calcein-AM) within a liposome to investigate whether the cargo disrupts membrane integrity.…”
Section: Assays That Measure Direct Interactions With Cytosolic Enzymesmentioning
confidence: 99%
“…One common example requires labeling a cargo with fluorescein-di-β- d -galactopyranoside (FDG, a di- O -glycosylated derivative of fluorescein). In this assay, the two sugars are cleaved off by β-galactosidase expressed in the cytosol of transfected cells, resulting in the unmasking of fluorescein. The dye is then localized and quantified by fluorescence microscopy and flow cytometry. ,, A similar system was reported that uses an acetoxymethyl ester of coumarin-cephalosporin-fluorescein (CCF2-AM), which is a FRET-based substrate probe developed specifically for Escherichia coli TEM-β-lactamase. , CCF2-AM exhibits green fluorescence, but its emission wavelength switches to blue upon cleavage by cytosolic β-lactamase, which was monitored by fluorescence microscopy and flow cytometry. , The cytosolic calcein release assay, originally developed to measure cell viability, involves either covalently labeling the cargo with calcein-AM, or coencapsulating the cargo with an acetoxymethyl ester version of calcein (calcein-AM) within a liposome to investigate whether the cargo disrupts membrane integrity. , When the nonfluorescent calcein-AM reaches the cytosol, it is cleaved by cytosolic esterases, releasing fluorescent calcein which can be measured by microscopy or flow cytometry. A similar assay using luminescence instead of fluorescence for more sensitive detection involves conjugation of the molecule to luciferin with a disulfide bond.…”
Section: Assays That Quantitate Cytosolic Localizationmentioning
confidence: 99%